Biomimetic confined self-assembly of chitin nanocrystals. (April 2022) - Liu, Peiwen; Wang, Jiaxiu; Qi, Houjuan; Koddenberg, Tim; Xu, Dan; Liu, Siyuan; Zhang, Kai
Highlights: The birefringent multi-layer hemicapsule-like and tube structures. The multi-dimensional gradient density and various spatial microstructures of self-assembled structures. The excellent stability of the self-assembly process to external interference. An accelerable self-assembly process. A fixed-boundary evaporation-induced self-assembly (FB-EISA) modality. Graphical Abstract: FB-EISA modality in this confined geometry provides a plausible routine to understand the generation of natural functional 3D structures from nanodomains. ga1 Abstract: It is a longstanding challenge to aptly describe the natural assembly process of chitin Bouligand organization as well as biomimetic construct these position-dependent structures with the isolated chitin nanodomains. Here, we report a fixed-boundary evaporation-induced self-assembly (FB-EISA) modality using chitin nanocrystals (ChNCs) in the capillaries, where the generation of continuous and ordered anisotropic phase relies on the growth of phase boundary towards the opposite direction of water evaporation. Distinct from the previous EISA modalities with the moving evaporation interface, the pinned air-liquid interface at the end of capillaries in a confined environment acts as the evaporation interface and initial deposition site of ChNCs simultaneously. During the whole self-assembly process via successive evaporation, the generation of droplets-like ChNCs clusters known as tactoids is suppressed. Therefore, continuous birefringent multi-layers as nested multiple paraboloid structures of ChNCs with a density gradient are gradually generated, before cylindrical tubes are formed finally. The FB-EISA process can be accelerated by heat and maintains stable regardless of vibration or different capillary opening directions relative to gravity direction. This FB-EISA modality in confined geometry allows rapid formation of ChNCs-based photonics-quality structure of larger length scales and enables us to deepen our understanding of the natural self-assembly process in diverse biological species.